2010
DOI: 10.1111/j.1750-3841.2010.01908.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Antioxidant and Antiproliferative Activities of Red and White Pitayas and Their Correlation with Flavonoid and Polyphenol Content

Abstract: Pitaya, commonly known as dragon fruit, has generated considerable consumer interest because of its attractive color and micronutrient content. The present study investigated the total polyphenol and flavonoid content, antioxidant activity against various free radicals, and antiproliferative effect on several cancer cell lines of extracts of flesh and peel of white and red pitayas, collected from Jeju Island, Korea. The total polyphenol and flavonoid contents of 80% methanol extracts of red pitaya peel (RPP) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
89
2
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(102 citation statements)
references
References 42 publications
5
89
2
6
Order By: Relevance
“…In some regions of South America, the pulp is used in beverages, as successfully occurs in Brazilian restaurants where it is served in chunks, together with champagne [7]. The red pitaya shell has great potential to be used as natural pigment due to the presence of betacyanin [8], and presents possible antioxidant activity [9]. In Brazil, there are a few farming areas dedicated to the pitaya cultivation, in the state of São Paulo, mainly in Catanduva County where production occurs from December to May, with an average annual yield of 14 tons of fruit per hectare [1].…”
Section: Introductionmentioning
confidence: 99%
“…In some regions of South America, the pulp is used in beverages, as successfully occurs in Brazilian restaurants where it is served in chunks, together with champagne [7]. The red pitaya shell has great potential to be used as natural pigment due to the presence of betacyanin [8], and presents possible antioxidant activity [9]. In Brazil, there are a few farming areas dedicated to the pitaya cultivation, in the state of São Paulo, mainly in Catanduva County where production occurs from December to May, with an average annual yield of 14 tons of fruit per hectare [1].…”
Section: Introductionmentioning
confidence: 99%
“…Alguns componentes obtidos da casca de pitaia vermelha e branca também demonstraram capacidade de inibir o crescimento de células cancerígenas (WU et al, 2006;KIM et al, 2011).…”
Section: Exploração E Uso Da Pitaia Vermelhaunclassified
“…Red dragon fruit skin has high antioxidant content when compared with its fruit flesh, such as phenolic, flavonoids, and polyphenols (Wu et al 2006). The polyphenols and flavonoids contained in red dragon fruit's methanol extract are five times higher than those in its fruit flesh (Kim et al 2011). Nurliyana et al (2010) proved that the content of phenolic compound on red dragon fruit skin was 28.16 mg/100 g while for the flesh was only 3.75 mg/100 g. Free radical binding activities conducted with IC50 technique also showed that red dragon fruit skin had the highest free radical binding activity.…”
Section: Introductionmentioning
confidence: 99%